Beckwith-Wiedemann Syndrome: deciphering the genetic and clinical complexity - A case report with literature review - Astrit M. Gashi; Brikene Elshani (Amaltea Medical Publishing House, 2023)
Beckwith-Wiedemann syndrome (BWS) is a rare and heterogeneous genetic condition characterized by overgrowth, organomegaly, and increased vulnerability to embryonal tumors. This review investigates the complex genetic and epigenetic pathways underlying Beckwith-Wiedemann syndrome, focusing on the 11p15.5 region on chromosome 11. Abnormalities in the 11p15.5 area, such as imprinting control region dysregulation and CDKN1C gene mutations, contribute to disrupted growth regulation. This content also provides an overview of the incidence and pathophysiology of this syndrome. Clinical manifestations include macrosomia, macroglossia, and abdominal wall abnormalities. The increased risk of embryonal malignancies, such as Wilms tumor and hepatoblastoma, emphasizes the importance of diligent medical observation. Early diagnosis through genetic testing is crucial for tailored management and genetic counseling. This detailed discussion of Beckwith-Wiedemann syndrome sheds light on the molecular complexities of the condition, emphasizing the significance of genetic testing, early detection, and multidisciplinary management for affected infants.